Path planning for robots: an elucidating draft - Sharma, Kaushlendra; Doriya, Rajesh (International journal of intelligent robotics and applications Online, 2020)
Proceeding for an elucidating draft for the robot’s path planning, there are several aspects which need to be addressed and discuss in detail. Some key points include the definition of the working environment, type of technique used to solve a particular type of problem, their subclassification and interdependencies with each other. It is also required to discuss in detail to understand and solve the problem of path planning in the right perspective. To do so, this paper presents the evolution of path planning algorithms of the last 5 decades, and then a broad classification of all those algorithms. After that, algorithms are categorized into different sections and has been discussed which are very often used in recent times to make the path planning approach more effective and efficient. This paper presents an extensive and elaborative survey of path planning algorithms and associated techniques for robots whose excellent contribution to the filed is invaluable. There are multiple issues related to the working environment of robots, whether it belongs to the two dimensional or three dimensional, static or dynamic, single robot or multi-robot, single objective/multi-objective and many more. This paper addresses all these issues in a detailed way. Another critical issue is related to the scope of algorithms which has been discussed at length in this paper like whether the algorithm is compatible for global/local path planning, it is Exact or heuristic in nature. This issue is systematically and hierarchically described to get a clear understanding of the problem domain. The effort is to bring an insight into the classification and evolution of path planning algorithms with its technical detail and discussions. The paper presents some emerging technologies which can be clubbed with robots to take it to another level. Cloud computing is one which is being extensively absorbed in many technologies. This paper discusses some cloud platforms like OpenStack and Google Cloud to deploy path planning applications for robots. This paper tries explicitly to conclude by testing path planning robots using Google cloud platform (using it as Infrastructure as a Service IaaS) citing its advantages and capability to expand its acceptability and assumes to be the future scope for robot path planning.